Village Fund Management On The Improvement Of Community Economy: english - Mainunah Sambas; Guntur Eko Saputro (CV. AFDIFAL MAJU BERKAH, 2024)
Village Fund management plays an important role in improving the economy of communities at the village level in Indonesia . A government policy known as Dana Desa provides funds to villages to support infrastructure development, community empowerment, and local economic growth. However, transparency, human resources, community participation, and project sustainability are some of the important issues in the management of the Dana Desa. The purpose of this study is to look at how the management of the Village Fund impacts the economic improvement of communities in villages. We used government data, academic studies, and related information to describe successful practices and emerging issues. The research used a literature study method that involved analysing relevant written sources. The results achieved that the local government in managing the Village Finance System can improve and not always change the existing system so that the village government is not confused anymore to run a new system so that policies can improve the efficiency of Village Fund management to support village economic growth.